Exploring the Perceptions of Middle School Teachers Regarding Response to Intervention Struggling Readers. Issue 4 (8th August 2022) - Thomas, Cathy Newman; Allen, Abigail A.; Ciullo, Stephen; Lembke, Erica S.; Billingsley, Glenna; Goodwin, Marilyn; Judd, Laura
ABSTRACT: Focus groups were conducted with middle school general and special education teachers to investigate their perceptions of Response to Intervention (RTI) reading intervention. Three cross-cutting themes emerged through content analysis: (a) the exigency of professional development, (b) buidling capacity to implement in middle school, and (c) teacher leadership. Participants supported the concept of RTI, but frustrations with feasibility were reported. Teachers implementing a standard-protocol expressed mixed perceptions. Future research should explore models that strengthen school capacity for middle school RTI and implications for professional development.